2020
DOI: 10.1111/geb.13077
|View full text |Cite
|
Sign up to set email alerts
|

Global gradients in intraspecific variation in vegetative and floral traits are partially associated with climate and species richness

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 119 publications
(170 reference statements)
4
49
0
1
Order By: Relevance
“…Moreover, the high seed traits variability among invasive Chilean Taraxacum officinale populations appeared to be highly correlated with variation in rainfall (Molina-Montenegro et al 2018) revealing the importance of environmental conditions and seasonality in determining seed traits variability. Recently, the study of global gradients for intraspecific trait variation with almost 3000 species revealed pronounced associations with climate (Kuppler et al 2020). Despite the idiosyncrasy of species-specific associations across gradients, in general, lower variation was observed in colder areas and higher in drier areas.…”
Section: Contributors To Seed Traits Variability: Geographic Distance Bioclimatic Conditions and Human Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the high seed traits variability among invasive Chilean Taraxacum officinale populations appeared to be highly correlated with variation in rainfall (Molina-Montenegro et al 2018) revealing the importance of environmental conditions and seasonality in determining seed traits variability. Recently, the study of global gradients for intraspecific trait variation with almost 3000 species revealed pronounced associations with climate (Kuppler et al 2020). Despite the idiosyncrasy of species-specific associations across gradients, in general, lower variation was observed in colder areas and higher in drier areas.…”
Section: Contributors To Seed Traits Variability: Geographic Distance Bioclimatic Conditions and Human Densitymentioning
confidence: 99%
“…However, the geographic variation of seed traits for a species, i.e., seed traits interpopulation variability, may come from different sources. Environmental heterogeneity, which includes climatic and habitat variability, is considered the main driver of intraspecific variability (Kuppler et al 2020) and may strongly contribute to interpopulation variability with the more similar populations under the more similar environmental conditions. It may be therefore assumed that geographic distance together with environmental distance (environmental dissimilarity) and habitat heterogeneity may determine interpopulation variability.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we collected leaf size data of both in situ and common garden populations of R. soongarica in northwest China to investigate how environmental and genetic differences affect leaf size variations in this species. Theoretically, intraspecific trait variation is affected by trade‐offs between abiotic stress and biotic factors (such as species richness and trait associations) (Agrawal, 2020; Kuppler et al., 2020). Considering the sparse vegetation and limited resources in ACA, we hypothesized that leaf size variations of this constructive shrub were more impacted by abiotic stress gradients.…”
Section: Introductionmentioning
confidence: 99%
“…1 black arrow). Specifically, the effects of temperature on plant quality (e.g., plant defense, palatability, tissue nutrients), growth rates, or phenology can vary considerably among taxa from different clades or functional groups (Herz et al 2017;Roybal & Butterfield 2019;Kuppler et al 2020;Hamann et al 2021;Sanczuk et al 2021;Sandel et al 2021) (but see Midolo et al 2019). Variation in how taxa within a community respond to changing temperature could result in thermal mismatch between the plant community and insect herbivores, and alter the role of phylogenetic or functional diversity in driving herbivory across temperature regimes.…”
Section: Introductionmentioning
confidence: 99%